HUBUNGAN KECERDASAN EMOSIONAL DENGAN PRESTASI BELAJAR PADA MAHASISWA PROGRAM D IV KEBIDANAN FK UNS - Erindra Budi C; Eny Qurniyawati (Wacana, 2010)
Midwives attitude of empathy, open and midwives awareness of feelings, thoughts experienced by the mother or her family is a midwife who has emotional intelligence. Therefore, emotional intelligence should be developed not only after working as a midwife, but also when she was sitting on a bench study. Curriculum and instructional design should be designed in such a way as to encourage  not just intellectual quotient  but also emotional quotient. This study aimed to determine the corelation between emotional quotient and academic achievement. Data collected by cross sectional study on 58 students in the last year of Midwifery School of FK UNS. Emotional intelligence was measured with a questionaire that has been tested for validity and reliability, and the student achievement showed by the student’s  7Th semester Grade Point Average (GPA) . Statistical analysis technique used Pearson Product Moment. Results showed that most students have a high emotional quotient (86%). The majority of student’s academic achievement is satisfactory (71%). Statistical analysis showed a  significant relationship of emotional quotient on student’s academic achievement , where t count is bigger than t table. Achievement of learning are supported by student’s ability to manage emotions in a way that positively affects the performance of duties, are sensitive to impulsive and unable to delay the enjoyment before reaching the target. Someone who can properly manage the emotions would be able to manage stress, cheerful, optimistic, calm in the face of every problem, and smart in determining problem-solving strategies, so that they can achieve optimal learning outcomes also according to research done by Rosyid (2008) and Wahyuningsih (2004).   Keywords : emotional quotient, academic achievement, Midwifery students